2007
DOI: 10.1007/s00125-007-0629-9
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol clearance and associations with insulin sensitivity, body fat and fatty liver in middle-aged men

Abstract: Aims/hypothesis The regulation of cortisol metabolism in vivo is not well understood. We evaluated the relationship between cortisol metabolism and insulin sensitivity, adjusting for total and regional fat content and for non-alcoholic fatty liver disease. Materials and methods Twenty-nine middle-aged healthy men with a wide range of BMI were recruited. We measured fat content by dual-energy X-ray absorptiometry and magnetic resonance imaging (MRI), liver fat by ultrasound and MRI, the hypothalamic-pituitary-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 43 publications
(47 reference statements)
3
25
0
1
Order By: Relevance
“…Our results show that there was an inverse relationship between cortisol clearance from the plasma and whole-body insulin sensitivity as measured by the hyperinsulinaemic-euglycaemic clamp in middle-aged men (mean age 53.0 years, mean BMI 32.0 kg/m 2 ) [2]. Importantly, we show that this relationship was independent of potential confounding factors such as body fat and fatty liver.…”
supporting
confidence: 49%
“…Our results show that there was an inverse relationship between cortisol clearance from the plasma and whole-body insulin sensitivity as measured by the hyperinsulinaemic-euglycaemic clamp in middle-aged men (mean age 53.0 years, mean BMI 32.0 kg/m 2 ) [2]. Importantly, we show that this relationship was independent of potential confounding factors such as body fat and fatty liver.…”
supporting
confidence: 49%
“…No study has investigated the effects of insulin on the metabolic clearance of adrenal hormones in hyperandrogenic women. Interestingly, Holt et al (17) showed that in men basal cortisol clearance negatively correlated with glucose clampderived measures of insulin sensitivity, thus suggesting a positive correlation with insulin levels.…”
Section: Discussionmentioning
confidence: 99%
“…The measure of hepatic insulin sensitivity that we derived from R a reflects wholebody endogenous glucose production during the early part of the hyperinsulinaemic clamp. We derived this measure from the data obtained during the early phase of the clamp, when glucose suppression was linear [25,26], because at the end of the clamp hepatic glucose output was completely suppressed in all individuals and therefore did not allow discrimination of liver insulin sensitivity between individuals. Unfortunately, it was not possible in these volunteers to also undertake a low-dose insulin clamp to assess suppression of hepatic glucose output.…”
Section: Discussionmentioning
confidence: 99%
“…For the Steele equations, 65% was used as the effective fraction and 0.22 l/kg as the distribution volume of glucose for calculation of R a and R d [22,24]. Hepatic insulin sensitivity was measured as insulin-mediated suppression of glucose output in the early part of the clamp and was expressed as percentage suppression 60 min after commencing the insulin infusion, when suppression was linear to this time point [25,26].…”
Section: Methodsmentioning
confidence: 99%